Faktor Risiko Aktivitas Fisik Pada Kejadian Diabetes Melitus Tipe 2 di Wilayah Kerja Puskesmas Kemaraya Kota Kendari Tahun 2023 - Risni Asrina Jati; Febriana Muchtar; Syefira Salsabila (Universitas Pahlawan Tuanku Tambusai, 2023)
Type 2 diabetes mellitus is a chronic disease characterized by a metabolic disorder that results in decreased insulin secretion or insulin resistance, leading to elevated blood glucose levels. This study was performed to assess the risk factors for Type 2 Diabetes Mellitus in the working area of the Kemaraya Public Health Center, Kendari City, in 2023, namely physical activty. This case-control study included patients who visited and underwent health checks at the Kemaraya Health Center in Kendari City in 2022 as population. A total of 90 samples were randomly selected and were divided into 45 cases and 45 controls. The results of this study revealed that physical activity (p value= 0.000, OR= 7.429; CI: 2.625-21.018), were significantly associated with Type 2 Diabetes Mellitus. In conclusion, physical activity were identified as the risk factors for the occurrence of Type 2 Diabetes Mellitus in the working area of the Kemaraya Public Health Center, Kendari City in 2023. Keywords: Type 2 diabetes mellitus; risk factor; physical activity